Membangun Etika Penggunaan Artificial Intelligence pada Pembelajaran Fisika di Materi Gerak Harmonik Sederhana - Nailatur Rohmah; Lailatul Qomariyah; Agus Budiyono; Sufijati Rifai (Mataram University, 2026)
Digital transformation has positioned artificial intelligence as a crucial instrument disrupting conventional learning methods. However, despite the rapid development of Artificial Intelligence (AI) utilization in physics education, ethical guidance for students exploring complex material independently remains limited, thus triggering the risk of academic integrity degradation. This study aims to formulate an ethical framework for the use of AI in physics learning on Simple Harmonic Motion (SHM) to mitigate this risk at the secondary level. Using a quantitative approach with a purposive sampling technique on 36 11th grade students in East Java, data were collected through profile questionnaires, AI-based worksheets as a material search medium, and an ethical perception scale. The findings show that AI use reached 92.3%, accompanied by significant ethical awareness (4.20) where students positioned AI as a discussion assistant, not a substitute for cognitive processes. Correlation analysis (0.43) proved that understanding the GHS concept increased students' accuracy in validating AI output. However, the transparency aspect acknowledged AI assistance as the lowest challenge (3.53). It was concluded that the use of AI does not compromise student integrity as long as it is accompanied by strengthened ethical perceptions and oversight by teachers as key supervisors. Therefore, educators are advised to integrate self-verification guidelines and ethical guidelines into technology-based assignments to maintain scientific honesty.